2022
DOI: 10.3390/ijerph19073886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Type of Sports Practice on the Executive Functions of Schoolchildren

Abstract: There is a close relationship between the development of complex motor skills and executive functions during childhood. This study aimed to analyze the differences in different dimensions of executive functions in children practicing an open-skill sport (handball) and a closed-skill sport (athletics) and controls who did not participate in sports activities after a 12-week intervention period. School-aged male and female subjects (n = 90; mean ± standard deviation = 11.45 ± 0.68 years) participated in a non-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 88 publications
0
9
1
Order By: Relevance
“…An interesting finding in this study is that EFs were not significantly increased in the conventional physical activities group over the intervention period, which contradicts earlier research concluding that longitudinal physical activity programs improved EFs [ 56 , 57 ]. This finding may be related to the short intervention period of only four weeks in this study; conventional physical activities with less cognitive involvement would barely have a significant influence on EFs in such a short period.…”
Section: Discussioncontrasting
confidence: 99%
“…An interesting finding in this study is that EFs were not significantly increased in the conventional physical activities group over the intervention period, which contradicts earlier research concluding that longitudinal physical activity programs improved EFs [ 56 , 57 ]. This finding may be related to the short intervention period of only four weeks in this study; conventional physical activities with less cognitive involvement would barely have a significant influence on EFs in such a short period.…”
Section: Discussioncontrasting
confidence: 99%
“…From an early age, executive functions are associated with physical activity [10][11][12][13][14], especially with the practice of sports [15][16][17][18][19]. Such a relationship has also been evidenced in older people, and associations have been reported between complex motor tasks and executive functioning [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one reason for the controversy in research on exercise interventions for executive function in atypical children is the different types of motor skills used in the studies (Shi, Tang, et al, 2022). And some studies (Contreras-Osorio et al, 2022;Koch & Krenn, 2021) (Zhang, 2012). Open skills are those that involve performing motor tasks in an unpredictable environment, where individuals need to react and adjust their movements to changes in the environment; closed skills are those that involve performing motor tasks in a stable, predictable environment, where individuals are able to plan their movement routines in advance (Zhang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one reason for the controversy in research on exercise interventions for executive function in atypical children is the different types of motor skills used in the studies (Shi, Tang, et al, 2022). And some studies (Contreras‐Osorio et al, 2022; Koch & Krenn, 2021) have shown variability in the effects of different types of motor skill interventions on executive function.…”
Section: Introductionmentioning
confidence: 99%